The soil food web revisited: Diverse and widespread mycophagous soil protists. (March 2016) - Geisen, Stefan; Koller, Robert; Hünninghaus, Maike; Dumack, Kenneth; Urich, Tim; Bonkowski, Michael
Abstract: Soil protists are commonly suggested being solely bacterivorous, serving together with bacterivorous nematodes as the main controllers of the bacterial energy channel in soil food webs. In contrast, the fungal energy channel is assumed to be controlled by arthropods and mycophagous nematodes. This perspective accepted by most soil biologists is, however, challenged by functional studies conducted by taxonomists that revealed a range of mycophagous protists. In order to increase the knowledge on the functional importance of mycophagous protists we isolated and initiated cultures of protist taxa and tested eight for facultative feeding on diverse fungi in microcosm experiments. Two different flagellate species of the genus Cercomonas, the testate amoeba Cryptodifflugia operculata and four genera of naked amoebae ( Acanthamoeba sp., Leptomyxa sp., two Mayorella spp. and Thecamoeba spp.) fed and grew on yeasts with four taxa ( Cercomonas sp., Leptomyxa sp., Mayorella sp., and Thecamoeba sp.) also thriving on spores of the plant pathogenic hyphal-forming fungus Fusarium culmorum . To identify the potential importance of mycophagous protists in the environment we applied a data-mining approach targeting small subunit (SSU) rRNA data obtained in metatranscriptomes of five fundamentally different terrestrial samples. We focused our analyses on the distribution and relative abundances of two well-studied mycophagous protist groups, vampyrellid amoebae and grossglockneriid ciliates. Both groups were detected in all of the highly contrasting terrestrial samples, comprising up to 3% of all protist SSU rRNA transcripts. SSU transcripts of these two groups, in contrast to all remaining protist SSU transcripts, showed strong correlations with the relative abundance of fungal sequences indicating close direct trophic interactions. Taken together, this study provides evidence that mycophagy among soil protists is common and might be of substantial but hitherto overlooked ecological importance in terrestrial ecosystems. Future studies should aim at evaluating taxon-specific (facultative) mycophagy, decipher changes caused in the fungal community and quantitatively evaluate the functional importance of this trophic position in soil ecosystems. Graphical abstract: Highlights: Many "bacterivorous" protists feed on fungi. Protists differentially feed on fungal taxa. Obligate mycophagous protists are present, abundant and active in soils. Mycophagy needs to be included protist functioning in future studies. Protist mycophagy should be considered in revised soil food web models.